Modificação de membranas de quitosana por plasma para uso biológico - Macêdo, Marina de Oliveira Cardoso (2009)
Chitosan membranes have been modified by plasma, utilizing the following gases: nitrogen (N2), methane (CH4), argon (Ar), oxygen (O2) and hydrogen. The modified membranes by plasma were compared to the unmodified ones. The membranes were characterized by absorption assay, contact angle, atomic force microscopy (AFM). Also, permeability assay of sodium sulfamerazine from such membranes were carried out. Through the absorption assay and contact angle it was possible to obtain information of the wettability of the membranes and what changes the plasma treatment can promote in relation to it. The plasma treatment using oxygen promoted increase of the wetability and swelling while the samples treated with methane decrease of the wetability and swelling. Through the Optical Emission Spectroscopy (OES) it was possible to identify which species were present in the plasma during the treatment. And through the AFM analysis it was possible to observe the changes nanotopography occurred on the surface of the samples. Permeability assay were archived for all treated membranes and compared to no treated ones. Due to that assay it was possible verify which the plasma treatment increased the permeability spectrum of the membranes which has varied from 1,4548 *10-5cm2.min-1 to 2,7713*10-5cm2.min-1. Chitosan membranes with permeability varied are importance in systems drug delivery, to liberate a wide variety of drugs